2019
DOI: 10.1038/s41598-019-38844-9
|View full text |Cite
|
Sign up to set email alerts
|

TNFα is responsible for the canonical offspring number-size trade-off

Abstract: There is a canonical life-history trade-off between quantity and quality of offspring, but molecular determinants for this are unknown. Here, we show that knockout of tumor necrosis factor (TNF-KO) in mice switched a relation between the number and size of developing embryos from expectedly negative to unexpectedly positive. Depletion of TNFα imbalanced humoral and trophic maintenance of embryo growth during gestation with respect to the litter size. The levels of embryotrophic GM-CSF cytokine and placental ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 38 publications
1
9
0
Order By: Relevance
“…We previously found that despite a decrease in odour attractiveness and sexual activity, immunised male mice showed a greater reproductive output when coupled with intact females who had no mating choice (Gerlinskaya et al 2012), which resulted in an increased embryo growth rate (Gerlinskaya et al 2017). In other words, the signalling and behavioural effects of antigenic stimuli do not diminish the male's reproductive abilities per se, and they can be fully realised in the absence of free mating choice.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…We previously found that despite a decrease in odour attractiveness and sexual activity, immunised male mice showed a greater reproductive output when coupled with intact females who had no mating choice (Gerlinskaya et al 2012), which resulted in an increased embryo growth rate (Gerlinskaya et al 2017). In other words, the signalling and behavioural effects of antigenic stimuli do not diminish the male's reproductive abilities per se, and they can be fully realised in the absence of free mating choice.…”
Section: Introductionmentioning
confidence: 98%
“…According to the life-history theory, host populations can respond to parasitic pressure by increasing their reproduction effort (Stearns 1992, McNamara & Houston 1996, Luu & Tate 2017. Effective reproduction under these conditions requires the preservation of reproductive potential despite the activation of innate and adaptive immunity.…”
Section: Introductionmentioning
confidence: 99%
“…5D). The usual inverse relationship between litter size and placental weight (Maslennikova, et al, 2019) was also lost (Fig. 5E), while the fetal:placental ratio and litter size were positively correlated in controls, but not after prednisolone treatment (Fig.…”
Section: Prednisolone Treatment Alters Fetal and Placental Weights And Removes The Fetal Weight To Litter Size Trade-offmentioning
confidence: 89%
“…The immune system is well-positioned to operate as an adaptive response to environmental signals in female control of reproductive investment (Robertson, 2010. Previous studies in mice implicate immune signals including maternal-fetal MHC disparity (Madeja, et al, 2011) and TNF expression (Maslennikova, et al, 2019) in female control of implantation rate. Thus we speculate that prednisolone suppresses a physiological mechanism through which the T cell population modulates the number of implanting embryos, in order to match maternal resource availability.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation